Penentuan Rute Pendistribusian Gas LPG Menggunakan Algoritma Prim dengan Optimalisasi melalui Pergantian Sisi - Syamsuddin Mas'ud (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research examines the determination of LPG gas distribution routes. The study is conducted on data collected by Elia Resita Ningrum in her research titled "Optimizing LPG Gas Distribution Routes Using the Floyd Warshall Algorithm and the Greedy Algorithm." This data is processed using different methods with the aim of obtaining better LPG gas distribution routes. The method to be used is the Prim algorithm, followed by route improvement through edge exchange in the graph. The Prim algorithm is used to obtain a minimum spanning tree. From this minimum spanning tree, one of the distribution routes is selected, namely v_1-v_2-v_3-v_4-v_8-v_4-v_10-v_11-v_10-v_4-v_5-v_6-v_7-v_9-v_12-v_13-v_14 with a total weight of 11.26. Route improvement is then carried out by exchanging edges in the graph, resulting in a new route, namely v_1-v_2-v_8-v_4-v_10-v_11-v_10-v_4-v_5-v_6-v_7-v_9-v_12-v_13-v_14 with a total weight of 10.91. This result is better than the result obtained by Elia Resita Ningrum with a total weight of 11.13. Based on the results obtained, for the case of LPG gas distribution by PT Petro Jaya Gas, the use of the Prim algorithm with route improvement through edge exchange produces better routes compared to the use of the Floyd Warshall Algorithm and the Greedy Algorithm conducted by Elia Resita Ningrum. Keywords: Route, Prim Algorithm, Edge Exchange.